This preview shows pages 1–8. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: + x . [6] S T ( x ) = 1F T ( x ) = 1Z x f T ( s ) ds = 1Z x ( + s ) +1 ds = ( + x ) 5 (b) Derive an expression for x . [5] x = f T ( x ) S T ( x ) = + x Note that f T ( x ) and S T ( x ) are given in the question. 6 (c) Derive an expression for S T x ( t ). [5] S T x ( t ) = S T ( x + t ) S T ( x ) = + x + t + x = + x + x + t . 7 (d) Using (b) and (c), or otherwise, nd an expression for f T x ( t ). [5] f T x ( t ) = S T x ( t ) x + t = + x + x + t + x + t . 8...
View Full
Document
 Summer '08
 MATTHEWTILL

Click to edit the document details